A theoretical study of allopurinol drug sensing by carbon and boron nitride nanostructures: DFT, QTAIM, RDG, NBO and PCM insights. Issue 61 (30th November 2021) - Miah, Md. Helal; Hossain, Md. Rakib; Islam, Md. Saiful; Ferdous, Tahmina; Ahmed, Farid
Abstract : The adsorption–desorption behavior of the drug allopurinol on/from the outer surface of a boron nitride nanocage was studied. Abstract : The application of low-dimensional nanomaterials in clinical practice as efficient sensors has been increasing day by day due to progress in the field of nanoscience. In this research work, we have conducted a theoretical investigation to nominate a potential electrochemical sensor for the allopurinol (APN) drug molecule via studying the fundamental interactions of the drug molecule with two nanocages (carbon nanocage/CNC – C24 and boron nitride nanocage/BNNC – B12 N12 ) and two nanosheets (graphene – C54 H18 and boron nitride – B27 N27 H18 ) by means of the DFT B3LYP/6-31G(d, p) level of theory in both gas and water phases. The adsorption energies of APN–BNNC conjugated structures are in the range of −20.90 kcal mol −1 to −22.33 kcal mol −1, which indicates that weak chemisorption has occurred. This type of interaction happened due to charge transfer from the APN molecule to BNNC, which was validated and characterized based on the quantum theory of atoms in molecules, natural bond analysis, and reduced density gradient analysis. The highest decreases in energy gap (36.22% in gas and 26.79% in water) and maximum dipole moment (10.48 Debye in gas and 13.88 Debye in water) were perceived for the APN–BNNC conjugated structure, which was also verified via frontier molecular orbital (FMO) and MEP analysis. Also, the highest sensitivity (BNNC > BNNS > CNC > GNS) and favorable short recovery time (in the millisecond range) of BNNC can make it an efficient detector for the APN drug molecule.